Analisis Pembuatan Trial Part Action Bracket Support Menggunakan Material SPHC dengan Metode FMEA dan Fishbone Diagram - Sayful Arif; Sumarjo, Jojo; Aripin, Aripin (Fakultas Teknik Universitas Tulang Bawang, 2025)
This research was conducted at PT Tri Jaya Teknik Karawang to analyze the constraints in making trial part action bracket support using SPHC T=3.2 material. This research is important because the trial part process is a crucial stage in ensuring production efficiency and product quality before entering the mass production stage, this research can reveal the root causes of defects, determine the main risk factors, and provide effective improvement recommendations. By applying the FMEA method, companies can reduce product defect rates, improve production efficiency, and optimize the use of resources. The Failure Mode and Effects Analysis (FMEA) method and fishbone diagram are used to identify failures, causes, and determine the highest failure value. This research plays a role in improving production efficiency by reducing the number of defective products that can cause waste of cost and time. The results show that the failures that have the highest Risk Priority Number (RPN) value are thread damage and off-center hole position with an RPN value of 180. Fishbone diagrams identify the main factors causing failures which include tapping, drilling, bending, and operators. Keywords: Failure Mode and Effects Analysis (FMEA), Fishbone Diagram, Manufacturing, Trial Part